2017
DOI: 10.1038/s41598-017-11525-1
|View full text |Cite
|
Sign up to set email alerts
|

Elemental and Molecular Segregation in Oil Paintings due to Lead Soap Degradation

Abstract: The formation of Pb, Zn, and Cu carboxylates (soaps) has caused visible deterioration in hundreds of oil paintings dating from the 15th century to the present. Through transport phenomena not yet understood, free fatty acids in the oil binding medium migrate through the paint and react with pigments containing heavy metals to form soaps. To investigate the complex correlation among the elemental segregation, types of chemical compounds formed, and possible mechanisms of the reactions, a paint sample cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…One significant consequence of the interaction is the formation of metal carboxylates, which can be detected by Fourier Transform Infrared (FTIR) spectroscopy [8] [10]. It has been shown that in the case of oil and metal-based pigments, the unbound fatty acids present inside the oleic binder bond to metal ions and, via a hopping mechanism, cause the migration of metal ions from the metal oxide to the binding medium where the metal ions attach to the polymer network and form metal carboxylates [11] [12]. Another mechanism suggested to occur in paint material is the adsorption of the organic acids on the pigment particle surface [10] [13].…”
Section: Introductionmentioning
confidence: 99%
“…One significant consequence of the interaction is the formation of metal carboxylates, which can be detected by Fourier Transform Infrared (FTIR) spectroscopy [8] [10]. It has been shown that in the case of oil and metal-based pigments, the unbound fatty acids present inside the oleic binder bond to metal ions and, via a hopping mechanism, cause the migration of metal ions from the metal oxide to the binding medium where the metal ions attach to the polymer network and form metal carboxylates [11] [12]. Another mechanism suggested to occur in paint material is the adsorption of the organic acids on the pigment particle surface [10] [13].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of metal carboxylates (soaps) has been reported in hundreds of oil paintings dating from the 15th to the 20th century. [1][2][3][4][5][6][7][8][9][10] Soaps are the result of reactions between metals in pigments or in other compounds present in the paints, such as driers or other modifiers, and long chain fatty acids originating in the binding medium or coatings. The triggering factors and underlying mechanisms behind the processes are not yet completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a micron-sized beam in XRF mapping, with scanning of the X-ray photon energy, allows micro-X-ray absorption near-edge structure (micro-XANES) spectroscopy across the Pb-M 4 and M 5 edges that permits differentiation of Pb pigments and Pb soaps. 9,34,35 Scanning electron microscopy (SEM), in combination with optical microscopy, has been applied to image the characteristic morphology of soap protrusions localized in the stratigraphy of paint crosssections. 36 Chromatographic and/or mass spectrometric techniques, such as gas chromatography-mass spectrometry (GC-MS), pyrolysis-GC-MS, secondary ion mass spectrometry (SIMS), high-performance liquid chromatography (HPLC), direct temperature-resolved mass spectrometry (DTMS), and related methods, have also been utilized in samples removed from works of art and in model paints to identify fatty acids involved in soap formation.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of methods have been used to characterize the reactive species, free fatty acids and pigments, and products of soap deterioration in both microsamples removed from artistic paintings and model paint samples (See, for example 1 , 3 , 5 , 6 , 16 – 22 ). Boon et al utilized neutron radiography on a mesoscopic level to study water uptake by model samples of painting canvas supports and ground preparations.…”
Section: Introductionmentioning
confidence: 99%